Probing for congenital nasolacrimal duct obstruction: a systematic review and meta-analysis of randomized clinical trials - Farat, Joyce Godoy [UNESP]; Schellini, Silvana Artioli [UNESP]; El Dib, Regina [UNESP]; Santos, Felipe Gasparini dos [UNESP]; Fernandes Sousa Meneghim, Roberta Lilian [UNESP]; Jorge, Eliane Chaves [UNESP] (Consel Brasil Oftalmologia, 2021)
Purpose: Lacrimal probing is the treatment of choice for congenital nasolacrimal duct obstruction that does not have a spontaneous resolution; however, there is no consensus about the best time for probing and if it is superior to other therapies. The present study aimed to evaluate the effectiveness of lacrimal probing compared with other treatments/no intervention to treat congenital nasolacrimal duct obstruction. Methods: A systematic review of literature in PubMed, EMBASE, CENTRAL, clinicaltrials. gov, and LILACS databases up to December 2019 was performed. Randomized clinical trials that enrolled children diagnosed with congenital nasolacrimal duct obstruction and undergoing lacrimal probing were considered. Data extraction and a risk of bias assessment were conducted independently and in duplicate. The overall quality of evidence for each outcome was conducted using the Grading of Recommendations, Assessment, Development, and Evaluation classification system. Results: Four randomized clinical trials involving 423 participants were eligible. No statistically significant differences were observed in resolution rates between early probing and observation/late probing (two studies; risk ratio 1.00 [95% confidence interval 0.76-1.33]; p = 0.99; low certainty evidence). One study reported better resolution rates with bicanalicular silicone stent intubation compared with late probing in the complex congenital nasolacrimal duct obstruction cases subgroup (risk ratio 0.56 [95% confidence interval 0.34-0.92]; p = 0.02; moderate certainty evidence). Conclusions: Low certainty evidence suggests that early probing has the same success rate as late probing. Evidence of moderate certainty suggests that late probing has a lower success rate than bicanalicular silastic intubation in patients with complex congenital nasolacrimal duct obstructione.
Keywords: Lacrimal duct obstruction/congenital; Lacrimal duct obstruction/therapy; Infant